2022
DOI: 10.3390/ijms23158286
|View full text |Cite
|
Sign up to set email alerts
|

Microglia as Therapeutic Target for Radiation-Induced Brain Injury

Abstract: Radiation-induced brain injury (RIBI) after radiotherapy has become an increasingly important factor affecting the prognosis of patients with head and neck tumor. With the delivery of high doses of radiation to brain tissue, microglia rapidly transit to a pro-inflammatory phenotype, upregulate phagocytic machinery, and reduce the release of neurotrophic factors. Persistently activated microglia mediate the progression of chronic neuroinflammation, which may inhibit brain neurogenesis leading to the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 253 publications
0
23
0
2
Order By: Relevance
“…After RIBI, microglia dysfunction, inflammatory factors such as TNF-α and IL-6 were released, and neuroimmune inflammation was triggered. 54 The expression of TNF-α and IL-6 in the model group and the blank MC group was significantly increased compared with the healthy group. The LMC could significantly reduce the TNF-α and IL-6 content in the serum compared with the model group (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…After RIBI, microglia dysfunction, inflammatory factors such as TNF-α and IL-6 were released, and neuroimmune inflammation was triggered. 54 The expression of TNF-α and IL-6 in the model group and the blank MC group was significantly increased compared with the healthy group. The LMC could significantly reduce the TNF-α and IL-6 content in the serum compared with the model group (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…After RIBI, microglia dysfunction, inflammatory factors such as TNF-α and IL-6 were released, and neuroimmune inflammation was triggered. 54 The expression of TNF-α and IL-6 in the model group and the blank MC group was significantly increased…”
Section: Highly Reduced Expression Of Inflammatory Cytokinesmentioning
confidence: 92%
See 1 more Smart Citation
“…Lipoplatin™ and Lipoxal™ liposomes show similar potency to carboplatin, but accumulate in brain tumors and show better therapeutic efficacy. 31 Therefore, to reduce toxicity, platinum drugs are encapsulated in liposomes for controlled drug delivery administered intravenously, intraarterially, or in combination with disruption of the blood-brain barrier. According to Taira et al, a similar therapeutic effect was observed with chemotherapy combined with cisplatin, vinblastine, and bleomycin (PVB therapy).…”
Section: Dose Determinationmentioning
confidence: 99%
“…Radiation also generates late effects and results in brain tumors and imposes neurocognitive disorders. 102 It decreases neurogenesis and differentiation, and causes alteration in neural structure and synaptic plasticity. Cell replacement therapy is used for restoration of memory and cognition deficits.…”
Section: Prostate Cancermentioning
confidence: 99%